Trust as a Mediator Between Personalization and Customer Loyalty in Indonesian E-Commerce - Nugraha Kusbianto; Billy Purwocaroko Noeringtyas; Budi Prabowo (Jurnal Manajemen, 2026)
Southeast Asia’s booming e-commerce industry underscores consumer loyalty as a strategic asset. Leading Indonesian platforms employ algorithmic personalization to tailor recommendations and interfaces, yet the role of trust in converting personalization into loyalty remains underexplored. Drawing on Social Exchange Theory and the Stimulus-Organism-Response framework, this study examines how personalization influences trust, engagement, satisfaction, and loyalty among Indonesian online shoppers. Data from an online survey of experienced users reveals that personalization enhances engagement and satisfaction, while engagement and trust drive loyalty. Satisfaction alone does not ensure loyalty, but trust fully mediates the personalization–loyalty relationship. The findings highlight trust as the crucial mechanism transforming personalized interventions into sustained loyalty. E-commerce firms should refine personalization algorithms and adopt transparent data practices to foster trust and lasting customer commitment.